2019
DOI: 10.1108/jadee-01-2019-0003
|View full text |Cite
|
Sign up to set email alerts
|

Motivation and barriers to access to formal credit of primary cinnamon producers from the perspective of value chain development in Northwestern Vietnam

Abstract: Purpose The purpose of this paper is to investigate borrowing motivation, credit access barriers and their impacts on income of smallholder farmers engaging in cinnamon value chain development in Northwestern Vietnam. Design/methodology/approach A multistage sampling technique using a structural questionnaire and in-depth interviews was applied for collecting primary data from farmers and relevant stakeholders. The Propensity Score Matching was employed to analyze access barriers and examine whether relaxing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 54 publications
1
8
0
Order By: Relevance
“…If the bank coverage is expanded, it would give clients a better access to the credit and reduce the impact of “black credit”. This barrier is almost similar to what Luan (2019) and Beck et al (2005) found. The results show that the loan volume is sufficient (2 = sufficient) and meets demand of the borrowers.…”
Section: Resultssupporting
confidence: 89%
See 1 more Smart Citation
“…If the bank coverage is expanded, it would give clients a better access to the credit and reduce the impact of “black credit”. This barrier is almost similar to what Luan (2019) and Beck et al (2005) found. The results show that the loan volume is sufficient (2 = sufficient) and meets demand of the borrowers.…”
Section: Resultssupporting
confidence: 89%
“…Johnston and Morduch (2008) found that distance could be a barrier for clients to access bank savings services in Mexico. Luan (2019) identified barriers of accessing formal credit of cinnamon growers in the Northwest of Vietnam included lack of collateral, bank accounts and geographical difficulties.…”
Section: Literature Reviewmentioning
confidence: 99%
“…While Teng et al (2011) evaluated the positive effect of microcredit on welfare of low-income households, Phan et al (2019) found an insignificant effect. A similar study has also shown that welfare does not appear to be driven by microcredit (Luan 2019). The study strongly stated that the provision of microcredit was able to enhance the financial status, health status and also education level of the low-income households.…”
Section: P R O O Fmentioning
confidence: 79%
“…The result suggested that PVS practically stimulated the participation and adoption of the attending farmers to the local market to purchase new seed varieties. Micro-credit, another form of government intervention, was also verified to significantly impact the approaching capability of Northwestern Vietnamese farmers in the study of (Luan, 2019). Consequently, market-access orientation has become a substantially irreplaceable content in extension training courses that directly support farmers to do their agribusiness sustainably by enhancing their pre-and post-harvest activities.…”
Section: Literature Reviewmentioning
confidence: 96%